INFLUENCE OF MATERNAL SOCIODEMOGRAPHIC FACTORS AND COMORBIDITIES ON NEONATAL CONGENITAL HEART DISEASE - Nurmukhambetova, Nuraiym (Nazarbayev University School of Medicine, 2025)
Introduction: The number of neonates with congenital heart disease is increasing. The incidence and development can be affected by certain maternal sociodemographic factors like age, residence, BMI, and comorbidities. Aims: This study aims to identify the incidence of congenital heart diseases among neonates in the National Research Center for Maternal and Child Health (NRCMCH), assess the maternal sociodemographic factors and comorbidities of the neonates with congenital heart disease, and evaluate the association of the development of congenital heart malformations with maternal sociodemographic factors and comorbidities. Methods: A population-based retrospective cohort study was conducted in NRCMCH in Astana from January 2024 to December 2024. All of the medical records of the neonates with congenital heart disease from this period will be collected. Frequency analysis, Chi-square test and binary logistic regression will be utilized to estimate the incidence of congenital heart defects and then evaluate the association with maternal sociodemographic factors and comorbidities. Results: Among the cohort of 616 neonates, 28.9 % were diagnosed with a congenital heart disease. There was a weak negative correlation between maternal age and congenital heart disease, (rpb = -.098, n = 613, p = .016). Neonates from rural areas are more likely to develop congenital heart malformations. There is a weak association between maternal BMI and congenital heart disease, Χ2 (2, N=410) = 12.061, p = 0.002, V = 0.172. There is no association between the presence of maternal hypertension or diabetes and the development of congenital heart disease in neonates. Conclusion: This research found that there are some associations between maternal sociodemographic factors and the development of congenital heart diseases in neonates. Particularly, maternal residence and BMI were correlated with a higher chance of getting congenital heart malformations. There was also the association with lower maternal age, which is consistent with other recent studies.
Keywords: congenital heart disease; neonates; sociodemographic factors; type of access: embargo